Effect of Soil pH on the Growth, Reproductive Investment and Pollen Allergenicity of Ambrosia artemisiifolia L. - Gentili, Rodolfo; Ambrosini, Roberto; Montagnani, Chiara; Caronni, Sarah; Citterio, Sandra (Frontiers in Plant Science, 2018)
Despite the importance of soil reaction for alien plant establishment, few and incomplete studies have included this key factor so far. In this study, we investigated the effects of soil pH on the germination, growth (plant height, width, dry weight, etc.) and reproductive investment (inflorescence size and n° of flowers) of Ambrosia artemisiifolia (common ragweed), an allergenic species that is highly invasive and alien in Europe, through a replicated experiment in controlled conditions. In addition, we determined if soil pH has an effect on the total pollen allergenicity of the species. After preliminary germination tests on agar at different pH (from pH4 to pH8), plants were grown in natural soils with pH values of 5 (acid), 6 (sub-acid) and 7 (neutral) obtained by modifying a natural soil by liming methods (calcium hydroxide solution). Results showed that plants grown at pH7 were shorter and developed leaves at a slower rate than those grown at pH5 and pH6; in addition, plants grown at pH7 did not produce flowers and pollen. We also observed that, at pH5 and pH6, larger plants (as assessed by the dry weight of the aerial biomass) had both larger and more numerous inflorescences and produced pollen emission earlier. Finally, the IgE-binding signal was higher in pollen samples collected from plants grown at pH5 (IOD range: 1.12-1.25) than in those grown at pH6 (Integrated Optical Density, IOD, range: 0.86 -1.03). Although, we acknowledge the limitations of only testing the effects of pH in controlled conditions, this study suggests that soil pH greatly affects the growth and development of A. artemisiifolia and indicates that soil pH may have a role in limiting the distribution and hazardousness of this plant. Future field tests should therefore assess the effectiveness of liming in the management and control of ragweed and other alien species.